4‐Fluoroamphetamine in the Netherlands: more than a one‐night stand. (19th May 2015) - Linsen, Felix; Koning, Raoul P. J.; van Laar, Margriet; Niesink, Raymond J. M.; Koeter, Maarten W.; Brunt, Tibor M.
Abstract Aims To investigate the temporal pattern of appearance of a new psychoactive substance (4‐fluoroamphetamine) on the Dutch drug market, as well as its patterns of use and effects. Design Data from the Drug Information and Monitoring System (DIMS) was used to investigate the emergence of 4‐fluoroamphetamine on the Dutch drug market. An on‐line questionnaire was used to study its patterns of use and effects. Setting Dutch drug‐related websites and social media. Participants A convenience sample of 249 life‐time 4‐fluoroamphetamine users was recruited through the internet. Measurements Samples containing 4‐fluoroamphetamine were extracted from the DIMS database for further investigation. Patterns of use, settings of use and the subjective effects of 4‐fluoroamphetamine, amphetamine and 3, 4‐methylenedioxymethamphetamine (MDMA) were investigated with the on‐line questionnaire. Findings 4‐Fluoroamphetamine was first encountered on the Dutch drug market, sold mainly as amphetamine or ecstasy (MDMA), between 2007 and 2009. These misrepresented drug samples declined when the MDMA and amphetamine markets recovered after a period of shortage, whereas purposefully bought 4‐fluoroamphetamine samples showed an increase. Survey results showed that 4‐fluoroamphetamine is used predominantly [77.1%, 95% confidence interval (CI) = 72.0–82.3] for its specific effects, rather than its legal status (17.7%, 95% CI = 10.7–22.1). The subjective effects of 4‐fluoroamphetamine were compared with those of amphetamine and MDMA. Subjective effect scores of 4‐fluoroamphetamine ranged between those of amphetamine and MDMA. Conclusions The stimulant 4‐fluoroamphetamine is increasingly popular in the Netherlands, which might be due to its subjective effects profile, which lies intermediate between amphetamine and MDMA.